Role of Micro Finance Institutions on the Social Economic Wellbeing of its Customers: A Case Study of Pride Microfinance Kabale Branch. - Natuhwera, Evas (Kabale University, 2024)
This study was carried out in pride microfinance bank, Kabale district-Uganda. It was aimed at establishing the role of Microfinance Institutions on economic well-being of its customers. The study was guided by three objectives namely: To find the effect of Microfinance Institutions towards the well-being of customers in pride microfinance banks, to establish the challenges hindering microfinance Institutions towards the well-being of its customers, to establish measures that can be adopted to solve challenges hindering the microfinance Institutions towards the well-being of customers in pride microfinance bank. The literature review for the study was extracted from different textbooks, manuals, reports, journals, and websites from different libraries and computer laboratories. The study employed descriptive cross-sectional research design. This involve case study to establish a causal relationship based on the results from some of the data collection tools which are questionnaire, participant observation and oral interviewing. The conclusion and recommendation of the study where drown based on how the effect of microfinance institutions contributed in the increase of sales of people’ products and chances to benefit from economic of scale and this improve the internal control of MFIS, training new inspectors and by increasing the number of on-site examination.